A porous vanadium oxide / carbon composite based on solvent exchange induced solidification and a preparation method and application thereof

CN122800592APending Publication Date: 2026-09-22HEXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611130564.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0007]本发明提供了一种基于溶剂交换诱导固化的多孔氧化钒/碳复合材料及其制备方法,旨在解决现有氧化钒基正极材料电子导电性差、Zn2+扩散动力学迟缓、充放电过程中结构易退化以及现有复合材料制备方法工艺复杂、复合均匀性不足、孔结构不可控等技术问题

Benefits of technology

1、本发明所得的多孔氧化钒/碳复合材料中,氧化钒活性组分均匀分布于连续导电碳网络骨架中,形成分级多孔孔道结构,该结构提高了电解液浸润能力,缩短了Zn2+扩散路径,增强了电子传输效率,从而缓解了循环过程中的结构退化,提升了Zn2+嵌入/脱出反应动力学,实现了优异的倍率性能及长循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122800592A_ABST
    Figure CN122800592A_ABST
Patent Text Reader

Abstract

This invention discloses a porous vanadium oxide / carbon composite material based on solvent exchange-induced curing, its preparation method, and its applications. The porous vanadium oxide / carbon composite material is formed by dispersing a vanadium oxide precursor and a structure regulator in an organic solvent to form a precursor system. This system undergoes solvent exchange-induced phase separation curing to form a three-dimensional network structure, followed by freeze-drying and heat treatment under an inert atmosphere to obtain the porous vanadium oxide / carbon composite material. When used as a cathode material in aqueous zinc-ion batteries, the obtained porous vanadium oxide / carbon composite material exhibits excellent electrolyte wetting ability, shortens the zinc ion diffusion path, and enhances electron transport capacity. This mitigates structural degradation during cycling, improves zinc ion insertion / extraction reaction kinetics, and results in superior rate performance and long-cycle stability. The preparation process of this invention is simple, the structure is controllable, and it is easy to implement, facilitating widespread application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrode materials technology for aqueous zinc-ion batteries, specifically to a porous vanadium oxide / carbon composite material constructed based on solvent exchange-induced curing, its preparation method, and its application. Background Technology

[0002] With the rapid development of portable electronic devices, grid energy storage, and renewable energy, developing novel energy storage devices with high safety, high energy density, and long cycle life has become an important research direction in the energy field. While lithium-ion batteries possess high energy density and are widely used in various energy storage scenarios, their application in large-scale energy storage is limited by uneven lithium resource distribution, high cost, and safety concerns. Therefore, developing resource-rich, environmentally friendly, and highly safe rechargeable battery systems is of great significance. Aqueous zinc-ion batteries, due to their abundant zinc resources, low cost, high safety, and high theoretical capacity, are considered a potential candidate system for next-generation large-scale energy storage technology. Among these, the cathode material, as the core component determining the electrochemical performance of zinc-ion batteries, directly affects the battery's capacity, rate performance, and cycle stability. Currently, vanadium-based oxides are favored due to their multi-valence reversible phase transition characteristics, high theoretical capacity, and suitable Zn content. 2+ Embedded channels have become a research hotspot in aqueous zinc-ion battery cathode materials.

[0003] However, traditional vanadium-based oxide cathode materials still have the following shortcomings in practical applications: Firstly, insufficient electronic conductivity. Vanadium oxide materials themselves have low electronic conductivity, which restricts electron transport within the electrode, resulting in significant electrode polarization at high current densities and limiting rate performance. Secondly, it has poor structural stability. Zn 2+ The repeated insertion / extraction process in the vanadium oxide lattice can easily cause lattice distortion, structural collapse and dissolution of active materials, resulting in rapid capacity decay and reduced cycling stability. Third, the ion diffusion kinetics are sluggish. The ion diffusion path inside vanadium oxide materials is relatively long, which limits the rapid transport of Zn²⁺ and affects the zinc storage capacity at high rates.

[0004] To address the aforementioned issues, existing technologies typically employ strategies such as carbon material composites, nanostructure design, and pore structure control to improve the electrochemical performance of vanadium oxide materials. For example, introducing conductive matrices such as graphene, carbon nanotubes, or porous carbon can, to some extent, enhance electron transport capabilities and mitigate structural changes. However, existing vanadium oxide / carbon composite materials still suffer from the following shortcomings in terms of preparation and performance: First, the composite uniformity is poor. The bonding force between the active component and the carbon matrix is ​​weak, making it prone to aggregation or phase separation, resulting in insufficient exposure of active sites and discontinuous electronic conduction pathways; Secondly, the pore structure is uncontrollable. There is a lack of effective pore construction strategies, making it difficult to form a hierarchical porous network structure, resulting in a single ion transport channel. Third, the utilization rate of active components is low. Due to the aforementioned defects in the composite and pore structure, the electrochemical activity of vanadium oxide is not fully released, resulting in an actual capacity far lower than the theoretical value.

[0005] Fourth, the existing preparation of porous vanadium oxide / carbon composite materials mainly relies on multi-step processing techniques such as hard template method, soft template method or etching-reassembly. These techniques have drawbacks such as complicated preparation process, difficulty in template removal, high cost, insufficient precision in pore structure control and limited large-scale production, which make it difficult to meet the needs of practical applications.

[0006] In summary, current technologies lack a simple process for effectively constructing vanadium oxide / carbon composite materials that combine a three-dimensional continuous conductive network and a hierarchical porous structure to synergistically enhance Zn content. 2+ Transport dynamics and the stability of the electrode structure. Summary of the Invention

[0007] This invention provides a porous vanadium oxide / carbon composite material based on solvent exchange-induced curing and its preparation method, aiming to solve the problems of poor electronic conductivity and Zn content in existing vanadium oxide-based cathode materials. 2+ The present invention addresses several technical challenges of zinc-ion batteries, including sluggish diffusion kinetics, structural degradation during charge and discharge, complex processes, insufficient composite uniformity, and uncontrollable pore structure in existing composite material preparation methods. By constructing a composite material with a three-dimensional continuous conductive network and an open, interconnected hierarchical pore structure, the invention simultaneously improves the electronic conductivity, ion transport efficiency, and structural stability of the material, thereby significantly enhancing the rate performance and cycle life of aqueous zinc-ion batteries.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: This invention provides a method for preparing porous vanadium oxide / carbon composite materials based on solvent exchange-induced curing, comprising the following steps: (1) Vanadium oxysulfate (VOSO4) was added to N,N-dimethylformamide (DMF) and dispersed evenly. Then, polyacrylonitrile (PAN) and polyvinylpyrrolidone (PVP) were added as structure regulators and mixed evenly to obtain a precursor dispersion system. (2) Add an aqueous exchange agent (preferably deionized water) to the precursor dispersion system, and induce the precursor dispersion system to solidify and assemble through solvent exchange to form a solid product with a three-dimensional network structure; (3) The solid product obtained in step (2) is freeze-dried; (4) The freeze-dried product is heat-treated under an inert atmosphere to obtain a porous vanadium oxide / carbon composite material.

[0009] The mass ratio of vanadium oxysulfate to polyacrylonitrile is 1:(5~20), preferably 1:(8~12); the mass ratio of polyvinylpyrrolidone to polyacrylonitrile is 1:(3~8), preferably 1:(4~6); and the mass fraction of vanadium oxysulfate accounts for 1%~10% of the total mass of the precursor system.

[0010] In step (2), the aqueous exchange agent is added continuously at a rate of 900 μL / min and a stirring rate of 500 r / min.

[0011] In step (3), the freeze-drying conditions are: temperature -30 ℃ and time 5-10 h.

[0012] In step (4), the inert atmosphere is a nitrogen atmosphere; the heat treatment temperature is 750~850℃, preferably 800℃; the holding time is 2~3 h, preferably 2.5 h; and the heating rate is 2~5℃ / min.

[0013] This invention also provides a porous vanadium oxide / carbon composite material, prepared using the above-described method. This composite material possesses a three-dimensional, interconnected hierarchical porous network structure, with the vanadium oxide active component uniformly distributed within a continuous conductive carbon network.

[0014] The present invention also provides the application of the above-mentioned porous vanadium oxide / carbon composite material in the cathode of an aqueous zinc-ion battery.

[0015] An aqueous zinc-ion battery cathode comprises the aforementioned porous vanadium oxide / carbon composite material.

[0016] Preferably, the preparation method of the aqueous zinc-ion battery positive electrode is as follows: by mass fraction, 70% porous vanadium oxide / carbon composite material, 20% conductive agent and 10% binder are mixed evenly, a dispersing solvent is added, and the mixture is stirred to form a uniform electrode slurry. The slurry is then coated on the surface of the current collector, dried and cut into electrode sheets to obtain the electrode.

[0017] More preferably, the conductive agent is carbon black (Super P), the binder is polyvinylidene fluoride (PVDF), the dispersing solvent is 1-methyl-2-pyrrolidone (NMP), and the current collector is graphite foil.

[0018] In this invention, vanadium oxysulfate is used as the vanadium source, which is converted into electrochemically active vanadium oxide during heat treatment. Polyacrylonitrile, as a carbon precursor, forms a three-dimensional continuous conductive carbon network after high-temperature carbonization. Simultaneously, the abundant cyano groups on its molecular chain can coordinate with vanadium ions, which is beneficial for the uniform anchoring and dispersion of vanadium species. Polyvinylpyrrolidone, as a structure regulator, regulates the assembly behavior of the precursor through its amphiphilic properties and decomposes to generate gas during heat treatment, thus playing a pore-forming role and promoting the formation of hierarchical porous structures. N,N-dimethylformamide, as a solvent, has good miscibility with water, providing a basis for the subsequent solvent exchange process.

[0019] The "solvent exchange-induced curing" described in this invention refers to the continuous dropwise addition of water to a DMF solution of vanadium oxysulfate / polyacrylonitrile / polyvinylpyrrolidone. Utilizing the complete miscibility of water and DMF, the solvent environment of the system is altered, reducing the solubility of polyacrylonitrile and polyvinylpyrrolidone in the mixed solvent. This induces phase separation and gelation of the polymer, while simultaneously promoting coordination crosslinking between vanadium species and polymer chains, thereby spontaneously assembling into a solid product with a three-dimensional network structure. This process differs from traditional volatilization-induced self-assembly (which relies on slow solvent evaporation to drive assembly), and features rapid assembly, uniform and controllable structure, without the need for template agents or multi-step processing.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. In the porous vanadium oxide / carbon composite material obtained by this invention, the vanadium oxide active component is uniformly distributed in the continuous conductive carbon network framework, forming a hierarchical porous channel structure. This structure improves the electrolyte wetting ability and shortens the Zn... 2+ The diffusion pathway enhances electron transport efficiency, thereby mitigating structural degradation during cycling and improving Zn content. 2+ The insertion / extraction reaction kinetics enable excellent rate performance and long-term cycling stability.

[0021] 2. This invention can achieve uniform composite and hierarchical porous structure construction of vanadium oxide precursor and carbon-containing precursor through solvent exchange, without the need for complex templates or multi-step processing. The process is simple, low-cost, and easy to promote and apply. Attached Figure Description

[0022] Figure 1 Scanning electron microscope (SEM) images at different magnifications of the porous vanadium oxide / carbon composite material prepared in the embodiments of the present invention.

[0023] Figure 2 The porous vanadium oxide / carbon composite electrode prepared for this embodiment of the invention operates at a current density of 0.1 A g. -1 The following is a graph showing the cyclic performance.

[0024] Figure 3 The electrochemical performance diagram of the porous vanadium oxide / carbon composite electrode prepared in the embodiments of the present invention is shown in the figure. Figure 3 (a) shows the electrode at a current density of 0.1 A•g -1 Constant current charge-discharge (GCD) curves at different cycle numbers; Figure 3 (b) represents the electrode at 0.1 A•g during the first 50 cycles. -1 The differential capacity (dQ / dV) curve is shown below.

[0025] Figure 4 The porous vanadium oxide / carbon composite electrode prepared for the embodiments of the present invention and the pure vanadium oxide electrode are compared at a current density of 5 A•g -1 The following is a comparison chart of the cycle performance. Detailed Implementation

[0026] The present invention will be further described in detail below through specific embodiments. These embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Experimental methods not specifically described in the embodiments are generally performed under conventional conditions or as recommended by the manufacturer.

[0027] Example 1 I. Preparation of porous vanadium oxide / carbon composite materials (1) Preparation of precursor dispersion system A certain amount of vanadium oxysulfate (VOSO4) was weighed and added to N,N-dimethylformamide (DMF) for thorough dispersion to obtain a homogeneous precursor solution. Subsequently, polyacrylonitrile (PAN) and polyvinylpyrrolidone (PVP) were added to the solution, where PAN and PVP act as structure modifiers to adjust the precursor structure and morphological evolution during subsequent carbonization. Under continuous stirring, the components were thoroughly mixed to form a homogeneous and stable precursor dispersion system. The mass ratio of vanadium oxysulfate to polyacrylonitrile was 1:10, and the mass ratio of polyvinylpyrrolidone to polyacrylonitrile was 1:5; the mass fraction of vanadium oxysulfate was 1%–10% of the total mass of the precursor dispersion system.

[0028] (2) Solvent exchange-induced curing process The above mixed solution was placed under stirring conditions, and deionized water was added dropwise as an aqueous solution exchanger to change the solvent environment of the system. This induced self-assembly between the vanadium oxide precursor and the carbon material, forming a solid product with a three-dimensional network structure. The dropwise rate of deionized water was 900 μL / min, and the stirring speed was 500 r / min. By controlling the solvent exchange process, a multi-scale porous structure was formed inside the solid product.

[0029] (3) Freeze-drying treatment The obtained solid product was subjected to freeze treatment, and the solvent in the system was removed by freeze-drying to obtain a composite material with a porous structure. The freeze-drying conditions were: temperature -30℃, time 5~10 h.

[0030] (4) High-temperature carbonization treatment The freeze-dried material was subjected to heat treatment under a nitrogen atmosphere to obtain a porous vanadium oxide / carbon (VO / C) composite material. The heat treatment conditions were: heating to 800℃ at a heating rate of 2~5 ℃ / min, and holding at that temperature for 2.5 h.

[0031] II. Battery Assembly The preparation process of the positive (cathode) electrode is as follows: 70% of the porous vanadium oxide / carbon composite material prepared above, 20% of the conductive agent carbon black (Super P), and 10% of the binder polyvinylidene fluoride (PVDF) are mixed evenly by mass fraction. An appropriate amount of 1-methyl-2-pyrrolidone (NMP) is added as a dispersion solvent, and the mixture is magnetically stirred until a uniform and viscous electrode slurry is formed. This slurry is uniformly coated onto the surface of a graphite foil current collector, and then dried in a vacuum oven at 60℃ for 12 h to remove the solvent. After drying, the electrode sheet is punched into circular pieces with a diameter of 12 mm, and its average loading is approximately 1.2 mg•cm. -2 .

[0032] Electrochemical performance testing was conducted using a CR2032 button half-cell system: the prepared electrode disc was used as the working electrode (cathode), a 12 mm diameter disc cut from 100 μm thick zinc foil was used as the counter electrode (anode), a 16 mm diameter Whatman GF / D glass fiber film was used as the separator, and a 2 M Zn(CF3SO3)2 aqueous solution was used as the electrolyte.

[0033] III. Structural Characterization and Performance Evaluation (1) Morphological characteristics The porous vanadium oxide / carbon composite material prepared in Example 1 was characterized by scanning electron microscopy (SEM), and the results are as follows: Figure 1 As shown. By Figure 1 It can be seen that the obtained composite material has a three-dimensional interconnected porous network structure. At low magnification ( Figure 1 (Left), the material exhibits a continuous skeletal morphology with a large number of uniformly distributed pores inside; at high magnification ( Figure 1 (Right) Abundant nanopores can be observed on the material surface, with interconnected pores forming a multi-scale porous structure. This structure indicates that the assembly behavior between vanadium oxide and carbon materials can be effectively controlled through solvent exchange-induced curing, promoting the formation of a composite material with an open-pore structure. The resulting hierarchical porous structure increases the contact area between the electrode material and the electrolyte, while shortening the Zn...2+ Diffusion pathways improve ion transport efficiency.

[0034] (2) Cyclic performance test (0.1 A•g⁻¹) Figure 2 The porous vanadium oxide / carbon composite electrode at 0.1 A•g was demonstrated. -1 Current density and cycling performance within the 0.2–1.8 V potential window. In the initial stage, the electrode capacity gradually increases to approximately 350 mAh•g⁻¹, exhibiting obvious activation characteristics. This phenomenon can be attributed to the gradual and sufficient wetting of the porous structure by the electrolyte, the gradual opening of ion transport channels, and a certain degree of structural rearrangement of the vanadium oxide lattice during cycling, exposing more electrochemically active sites. After the activation stage, the electrode capacity shows a slow decay trend, maintaining approximately 150 mAh•g⁻¹ after 50 cycles. -1 The reversible capacity was achieved, and the coulombic efficiency was increased to nearly 100% and remained stable during subsequent cycles, indicating that this porous composite electrode exhibits excellent performance in Zn. 2+ The intercalation / extraction process exhibits high electrochemical reversibility. Excellent cycle stability is primarily attributed to the constructed porous network structure, which facilitates rapid electrolyte wetting and Zn extraction. 2+ It enables efficient transport and, at the same time, mitigates the structural changes of vanadium oxide during the cycling process.

[0035] (3) Constant current charge and discharge and differential capacity analysis Figure 3 (a) shows the constant current charge-discharge curves of the porous vanadium oxide / carbon composite electrode at a current density of 0.1 A g⁻¹ for different cycle numbers. The high capacity observed during the initial discharge indicates a significant activation process in the initial stage of the electrode. With increasing cycle number, the overall profile of the charge-discharge curves remains highly consistent, indicating good electrochemical reversibility of the Zn²⁺ insertion / extraction process. Although there is some increase in polarization during long cycles, a clear plateau region is maintained, indicating that the electrode maintains stable reaction kinetics. To further elucidate the electrode reaction mechanism, Figure 3 (b) The dQ / dV curves at different cycle numbers were analyzed. Multiple obvious redox peaks appeared in the first cycle, indicating that Zn 2+ A multi-step insertion / extraction process exists within the vanadium oxide lattice. With continued cycling, the redox peaks gradually stabilize, indicating that the electrode undergoes an initial activation process, while the electrode-electrolyte interface gradually optimizes. From the 10th to the 50th cycle, the peak positions remain largely stable, demonstrating the good structural stability and reversibility of the porous vanadium oxide / carbon composite structure. Furthermore, the porous structure effectively reduces electrode polarization and promotes Zn... 2+ Rapid spread.

[0036] (4) High current cycling performance test (5 A•g) -1 ) Figure 4 As shown, at 5 A•g -1 At high current densities, the VO / C composite material prepared in this invention exhibits excellent cycling stability. After 500 cycles, VO / C still maintains a high reversible specific capacity (approximately 100 mAh•g). -1 ), while the VO material showed significant capacity decay (capacity approximately 30 mAh•g). -1 Meanwhile, the coulombic efficiency of the VO / C composite material remained stable at close to 100% over a long period, indicating that the composite structure can effectively improve the material's electrical conductivity, increase charge transfer efficiency, and suppress structural degradation during cycling, thereby achieving more stable energy storage performance.

[0037] In summary, the porous vanadium oxide / carbon composite material and its preparation method based on solvent exchange-induced curing provided by this invention are simple in process, low in cost, and controllable in structure. When the prepared composite material is used as a cathode material for aqueous zinc-ion batteries, it exhibits excellent rate performance and cycle stability, and has good industrial application prospects and industrialization value. It can be widely used in large-scale energy storage systems in portable electronic devices, grid energy storage, and renewable energy fields.

Claims

1. A method for preparing porous vanadium oxide / carbon composite materials based on solvent exchange-induced curing, characterized in that, Includes the following steps: (1) Vanadium sulfate was added to N,N-dimethylformamide and dispersed evenly. Then, polyacrylonitrile and polyvinylpyrrolidone were added as structure regulators and mixed evenly to obtain a precursor dispersion system. (2) Add deionized water to the precursor dispersion system and induce the precursor dispersion system to solidify and assemble through solvent exchange to form a solid product with a three-dimensional network structure; (3) The solid product obtained in step (2) is freeze-dried; (4) The freeze-dried product is heat-treated under an inert atmosphere to obtain a porous vanadium oxide / carbon composite material.

2. The method for preparing a porous vanadium oxide / carbon composite material based on solvent exchange-induced curing according to claim 1, characterized in that, In step (1), the mass ratio of vanadium oxysulfate to polyacrylonitrile is 1:(5~20); the mass ratio of polyvinylpyrrolidone to polyacrylonitrile is 1:(3~8); and the mass fraction of vanadium oxysulfate accounts for 1% to 10% of the total mass of the precursor system.

3. The method for preparing a porous vanadium oxide / carbon composite material based on solvent exchange-induced curing according to claim 1, characterized in that, In step (2), the deionized water is added continuously at a rate of 900 μL / min and a stirring rate of 500 r / min.

4. The method for preparing a porous vanadium oxide / carbon composite material based on solvent exchange-induced curing according to claim 1, characterized in that, In step (3), the freeze-drying conditions are: temperature -30 ℃ and time 5~10 h.

5. The method for preparing a porous vanadium oxide / carbon composite material based on solvent exchange-induced curing according to claim 1, characterized in that, In step (4), the inert atmosphere is nitrogen atmosphere; the heat treatment temperature is 750~850℃, the holding time is 2~3 h, and the heating rate is 2~5℃ / min.

6. A porous vanadium oxide / carbon composite material, characterized in that, It is prepared by the method described in any one of claims 1 to 5.

7. A positive electrode for an aqueous zinc-ion battery, characterized in that, It includes the porous vanadium oxide / carbon composite material as described in claim 6.

8. The aqueous zinc-ion battery positive electrode according to claim 7, characterized in that, The preparation method of the positive electrode of the aqueous zinc-ion battery is as follows: 70% porous vanadium oxide / carbon composite material, 20% conductive agent and 10% binder are mixed evenly by mass fraction, a dispersing solvent is added, and the mixture is stirred to form a uniform electrode slurry. The slurry is then coated on the surface of the current collector, dried and cut into electrode sheets to obtain the electrode.

9. The aqueous zinc-ion battery positive electrode according to claim 8, characterized in that, The conductive agent is carbon black, the binder is polyvinylidene fluoride, the dispersing solvent is 1-methyl-2-pyrrolidone, and the current collector is graphite foil.